Community Outbreak of OXA-48–Producing Escherichia coli Linked to Food Premises, New Zealand, 2018–2022 - Craig N. Thornley; Matthew Kelly; Max Bloomfield; Loushy Mangalasseril; Annette Nesdale; Claire Underwood; Kristin Dyet; Juliet Elvy; Jenny Szeto; Hermes Perez; Xioayun Ren; Rosemary Woodhouse; et al. (Emerging Infectious Diseases)
In New Zealand, OXA-48–producing Escherichia coli is uncommon and typically associated with international travel. We investigated a cluster of 25 patients without recent travel history from Hutt Valley health district, New Zealand, who had multilocus sequence type 131 OXA-48–producing E. coli during August 2018–December 2022. Eighteen had been admitted to Hutt Valley Hospital but did not share a common ward or hospital service. Eighteen had visited the same community-based commercial food premises (premises A); 7 of those had not been admitted to Hutt Valley Hospital. An inspection of premises A revealed multiple hazards, primarily around staff hand hygiene. Four food handlers were colonized with OXA-48–producing E. coli; whole-genome sequencing confirmed genomic links between case and food handler strains, with possible introduction to New Zealand circa 2017. Community-based food premises have a role in propagating OXA-48–producing E. coli in high-income countries, requiring consideration in control strategies.